In vitro and in-silico inhibitory validation of Tapinanthus cordifolius leaf extract on alpha-amylase in the management of type 2 diabetes - Amarachi Chike-Ekwughe; Abayomi Emmanuel Adegboyega; Titilayo Omolara Johnson; Abiodun Humphrey Adebayo; Olubanke Olujoke Ogunlana (Informatics in Medicine Unlocked, 2023)
Tapinanthus cordifolius an African mistletoe is an important medicinal plant that has been shown to lower postprandial hyperglycemia. It has been proposed that mistletoe's hypoglycemic effects are related to its ability to lower blood glucose levels and that the anti-diabetic activity of some of these parasitic plants might be due to their ability to block the action of alpha-amylase. To identify prospective alpha-amylase inhibitors for anti-diabetic drug discovery, the current study used in vitro experiments and computational methods such as molecular docking, pharmacophore modelling, and ADMET profiling to evaluate the alpha-amylase inhibitory ability of Tapinanthus cordifolius leaf extracts and its bioactive components. The crude extract of the plant showed the highest inhibiting activity with an IC50 value of 26.88 μg/ml. Gas chromatography-mass spectroscopic analysis of the extract gave 43 phytochemicals, including sesquiterpenes, diterpenes, triterpenes and their derivatives, phytosterols, and tocopherols. The molecular docking analysis of these compounds with alpha-amylase identified benzaldehyde, 4-(Ethylthio)-2,5-dimethoxy, alpha-Tocopherol-Beta-D-Mannoside, 5-ergosterol, 3,4,5-trimethoxybenzoic acid, and acetosyringone as the five top-scoring compounds. Their binding energies which ranged from −4.944 to −4.365 kcal/mol, were close to that of the reference compound, which was −5.67 kcal/mol. Like the reference ligand, these compounds interacted with crucial active site amino acid residues of alpha-amylase. They also possess favorable drug-like properties as well as a low-risk profile. Hence, these compounds could be subjected to lead optimization and experimental studies for further development into novel drugs for managing type 2 diabetes mellitus.